Non-conventional meals and cakes in ruminants - PRUSTY, SONALI; SWAIN, PARTHA SARATHI; SHARMA, VIJAY KUMAR (The Indian Journal of Animal Sciences, 2019)
A comprehensive review on nutritive value of non-conventional meals and cakes, viz. sal seed meal, neem cake, castor oil cake, karanj cake, rubber seed meal, guar meal and palm kernel cake, their safe levels of inclusion in ruminant diet and various processing methods for their detoxification was carried out. CP content in above feeds was well above 20% except sal seed meal (14%). Among several methods water washing, soaking, steam cooking, chemical and biological methods were the most abundantly tried by the researchers. Chemical treatment was effective in reducing toxic principles from sal seed meal (80–90%), neem seed cake, castor oil cake (around 100%) and karanj cake. In several cases, water washing after chemical treatment resulted in huge loss of dry matter (DM). Biological treatment with fungal culture was successful for the safe inclusion of guar meal and rubber seed cake. Thus non-conventional ingredients on detoxification hold a great promise in reducing the competition for feedstuff among human and ruminants and also in balancing ruminant ration.